2015
DOI: 10.1002/ejic.201500782
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Ammonium Citrate – What's in It?

Abstract: Ferric ammonium citrate (FAC) is administered to humans in drugs or food supplements, but its exact composition and structural features are not known. We report that the major component in commercial FAC‐brown and FAC‐green is a trinuclear ferric citrate complex, namely [Fe3(cit)4H]6– (1). Complex 1 comprises a dinuclear subunit in which two ferric ions with a 3.122(1) Å separation are bridged by two alkoxido oxygen atoms from two citrate ligands. Two other alkoxido oxygen atoms form a bridge to a third ferric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…31 Therefore, the bulky size of AFC makes it impossible to diffuse into the small pore of ZIF-7, and AFC molecules only anchor onto the surface of ZIF-7. 32 The ion-exchange reaction between Zn 2+ and Fe 3+ ions was evaluated by theoretical calculations. 33 The doping energy of Fe 3+ from AFC and ionized Fe 3+ to the skeleton of 3D ZIF-7 is 1.32 eV and −2.43 eV, respectively (Figures S1 and S2 in the Supporting Information), suggesting that the metal-ion exchange between AFC and ZIF-7 could be excluded due to the strong interaction between citrate ions and Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…31 Therefore, the bulky size of AFC makes it impossible to diffuse into the small pore of ZIF-7, and AFC molecules only anchor onto the surface of ZIF-7. 32 The ion-exchange reaction between Zn 2+ and Fe 3+ ions was evaluated by theoretical calculations. 33 The doping energy of Fe 3+ from AFC and ionized Fe 3+ to the skeleton of 3D ZIF-7 is 1.32 eV and −2.43 eV, respectively (Figures S1 and S2 in the Supporting Information), suggesting that the metal-ion exchange between AFC and ZIF-7 could be excluded due to the strong interaction between citrate ions and Fe 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…To date, the crystal structures of five ferric citrate complexes are known in the literature (Fig. 2); these consist of one mononuclear species, [FeCitrate 2 ] 5− (complex 1 ) [45]; two dinuclear species, [Fe 2 Citrate 2 (H 2 O) 2 ] 2− (complex 2 ) and [Fe 2 (HCitrate) 3 ] 3− (complex 3 ) [46]; one nonanuclear species, [Fe 9 OCitrate 8 (H 2 O) 3 ] 7− (complex 4 ) [47]; and one trinuclear species, [Fe 3 Citrate 4 H] 6− (complex 5 ) [48]. Ferric citrate complex 2 appears to be particularly relevant to the physiologic interactions.…”
Section: Chemical Composition Of the Active Pharmaceutical Ingredientmentioning
confidence: 99%
“…Green-blue spheres represent iron atoms, red spheres represent oxygen atoms, and gray spheres represent carbon atoms. Cit citrate.Based on data from Matzapetakis et al [45]; Shweky et al [46]; Bino et al [47]; and Tenne et al [4548]…”
Section: Chemical Composition Of the Active Pharmaceutical Ingredientmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has shown that iron encapsulated in liposomes can be absorbed effectively by intragastric administration [ 10 ], and nanoliposomes have been predicted to be even more efficient for carrying cargo across the BBB due to their optimized size, shape and surface coating [ 9 , 11 ]. Ferric ammonium citrate (FAC) is a water soluble iron chelate that has been used as an iron supplement [ 12 ]. However, FAC does not efficiently enter the brain due to the regulation of the iron uptake proteins in BBB [ 13 ].…”
Section: Introductionmentioning
confidence: 99%